Engineering molecular topology: A pseudopeptidic macrocyclic figure-eight motif - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P.; Butcher, Ray; Haridas, V. (European Journal of Organic Chemistry, 2017)
We herein present a rational-design strategy for the synthesis of molecules with figure-eight topology. The design concept is based on the incorporation of turn units in the back-bone of the macrocycle. The molecular structures and the folding are studied by X-ray crystallography and NMR, FT-IR, and CD spectroscopy.
Keywords: Macrocycles; noncovalent interactions; Pi interactions; topology; X-ray diffraction

Synthesis, characterization, Hirshfeld surface, cytotoxicity, DNA damage and cell cycle arrest studies of N, N-diphenyl-N `-(biphenyl-4-carbonyl/4-chlorobenzoyl) thiocarbamides - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano; Kaur, Manpreet; Jasinski, Jerry P. (Journal of Molecular Structure, 2019)
The condensation reaction of biphenyl-4-carbonyl isothiocyanate/4-chlorobenzoyl isothiocyanate with diphenylamine yielded two new compounds; N-diphenyl-N'-(biphenyl-4-carbonyl) thiocarbamide (1) and N, N-diphenyl-N'-(4-chlorobenzoyl) thiocarbamide (2). Structure of the compounds were determined by analytical, spectroscopic (UV-Visible, FT-IR, H-1, & C-13 NMR), powder and single-crystal X-ray diffraction methods. Hirshfeld surface analysis and their associated two dimensional fingerprint plots of compounds were used as theoretical approach to assess driving force for crystal structure formation via the intermolecular interactions in their crystal lattices. The compounds were screened for their in vitro cytotoxicity activity against a panel of five human cancer cell lines namely; cervical (2008 and C13*) and ovarian carcinoma (A2780, A2780/CP and IGROV-1). Both the compounds exhibited promising activity against cervical and IGROV-1 cancer cells whereas for the other two cell lines appreciable activities were observed. The cell cycle arrest at G(0)/G(1) phase is supported by the DNA damage and apoptosis studies of the compounds against 2008, C13* and IGROV-1 cell lines. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: DNA damage and cell cycle arrest; Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure

Synthesis, characterisation, Hirshfeld surface and in vitro cytotoxicity evaluation of new N-aryl-N `-Alkoxycarbonyl thiocarbamide derivatives - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano; Kaur, Manpreet; Jasinski, Jerry P. (Journal of Molecular Structure, 2020)
Four new compounds N-(4-nitrophenyl)-N'-(isobutoxycarbonyl) thiocarbamide (1), N-(2, 4-nitrophenyl)-N'-(isobutoxycarbonyl) thiocarbamide (2), N-(4-nitrophenyl)-N'-(ethoxycarbonyl) thiocarbamide (3) and N-(2-Chloro- 4-nitrophenyl)-N'-(ethoxycarbonyl) thiocarbamide (4) were prepared and their structures confirmed by using various spectroscopic (FT-IR, UV-Visible, H-1 and C-13 NMR) and single crystal X-ray studies of 1 and 3. The presence of intramolecular (N-H center dot center dot center dot O=C) hydrogen bond in the crystal structure of both the compounds causes planarity of carbonyl thiocarbamide unit and trans orientation of C=O and C=S group. The intermolecular contacts (C-H center dot center dot center dot S, C-H center dot center dot center dot O and N-H center dot center dot center dot S) present in crystal structures have been examined by Hirshfeld surface analysis and their associated 2D fingerprint plots. All the compounds were assessed for their in vitro cytotoxic properties against a panel of seven human cancer cells such as cervical carcinoma (2008, C13*), colorectal (HT29 and HCT116) and ovarian carcinoma (A2780, A2780/CP and IGROV-1). Among them, compounds 2 and 4 exhibited better activity than 1 and 3 against all the cell lines tested. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure